METACOGNITIVE AWARENESS OF READING STRATEGIES AMONG SOPHOMORE FAST-TRACK STUDENTS AT THE UNIVERSITY OF LANGUAGES AND INTERNATIONAL STUDIES = SIÊU NHẬN THỨC VỀ CHIẾN LƯỢC ĐỌC CỦA SINH VIÊN CHẤT LƯỢNG CAO NĂM HAI, KHOA SƯ PHẠM TIẾNG ANH, TRƯỜNG ĐẠI HỌC NGOẠI NGỮ, ĐẠI HỌC QUỐC GIA HÀ NỘI - Phạm, Ngọc Trâm (2020)
A number of studies around the world have laid focus on investigating the effect of metacognitive strategies in EFL learning, specifically in reading comprehension. The findings of these studies suggest that metacognitive strategies have a positive correlation with learners’ reading comprehension (Do & Nguyen, 2014). As an attempt to contribute more evidence to these previous findings, the present study investigated the metacognitive awareness of reading strategies that college students used in reading academic materials and the hindrance to their use of these strategies. The paper focused on the context of the Faculty of English Language Teacher Education, University of Languages and International Studies (FELTE, ULIS). For the accomplishment of these purposes, an adapted version of Survey of Reading Strategies (SORS), which consists of three broad categories of reading strategies namely, Global Reading Strategies, Problem-solving Strategies and Support Strategies, was conducted on 78 second-year students in the fast-track program. Then, among all participants, 4 students were selected for semi-structured interviews.